Effect of Chinese chives and perilla seed incorporation on physicochemical, functional properties and sensory attributes of pork sausage - Govindasamy Kadirvel
Meat and meat products, apart from being highly nutritious, comes with several health risk factors as they are also high in saturated fatty acids which can trigger various health issues. This can be modified functionally by incorporating various herbs, spices, fruits and vegetables that has functional properties benefiting the human health. Attempt has been made in this study to investigate the benefits ofincorporation of two such functional ingredients, viz., Chinese chives and perilla seeds to pork sausage. The resultant products were analyzed forproximate composition, biochemical properties and sensory attributes. Storage study was conducted and evaluated based on five parameters, viz., pH, WHC, Cooking loss, Cooking yield and Shrinkage percentage. Addition of functional ingredients has improved the sensory attributes and enhanced the antioxidant capacity and physiochemical properties of the product. Improved texture of pork sausage with functional herbs has led to decreased cooking loss and shrinkage percentage and increased cooking yield and WHC. Commercialization of these functional meat products will create a better market opportunity and benefit the consumers in the world.